2022
DOI: 10.1097/lbr.0000000000000859
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Endobronchial Valve Placement for Bronchoscopic Lung Volume Reduction

Abstract: Background: Patients with advanced emphysema experience breathlessness due to impaired respiratory mechanics and diaphragm dysfunction. Bronchoscopic lung volume reduction (BLVR) is a minimally invasive bronchoscopic procedure done to reduce hyperinflation and air trapping, promoting atelectasis in the targeted lobe and allowing improved respiratory mechanics. Real-world data on safety and complications outside of clinical trials of BLVR are limited. Methods: We queried the US Food and Drug Administrations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Recently published data from the CELEB trial showed an incidence of pneumothorax as high as 30.4% [ 15 ]. Another study found that 43% of cases were complicated by pneumothorax needing additional treatment for persistent air leak besides chest drain [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published data from the CELEB trial showed an incidence of pneumothorax as high as 30.4% [ 15 ]. Another study found that 43% of cases were complicated by pneumothorax needing additional treatment for persistent air leak besides chest drain [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upon manual review, 135 articles with unclear queries 32–164 and 120 with incomplete queries 165–284 were excluded. Ultimately, 60 executable queries were found 5,10,285–342 . A comprehensive flowchart of this selection process is depicted in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…In spite of the potential benefits, the EBV placement procedure is associated with risk of complications, for example, pneumothorax that is seen in 4.2%–26.6% of the treated patients, 7 and not all patients achieve the expected outcome. 7 , 8 Moreover, patients are faced with the decision to receive EBV treatment at a point in their disease trajectory where there are only few remaining treatment options and an outlook toward worsening of life-limiting symptoms in the future. Healthcare providers play a significant role in patients’ decision-making process.…”
Section: Introductionmentioning
confidence: 99%